Social Identity and Redistributive Preferences: A Survey - Joan Costa-i-Font; Frank Cowell (Center for Economic Studies and ifo Institute (CESifo), 2013)
Social identity has become accepted as a key concept underpinning the endogeneity of economic behaviour and preferences. It is important in explaining attitudes towards redistribution and pro-social behaviour. We examine how economic theory measures social identity and its effects on preferences towards redistribution, social solidarity and redistributive institutions. Empirical evidence indicates that social identity carries weight in explaining the presence of social preferences and attitudes towards redistributive institutions.
Keywords: H10; I30; 330; social identity; preferences for redistribution; inequality; diversity; redistributive institutions